A weighted unification yield criterion and its application in analysis of burst pressure of pipe elbow. (15th December 2021) - Zhang, Shun Hu; Liu, Jia Rong; Liu, Xin Ying
Abstract: In order to solve the problem of insufficient accuracy in predicting the burst pressure of a pipe elbow based on the existing yield criteria, a new yield criterion is established firstly and then used to analyze the plastic failure of a pipe elbow. According to this idea, the mathematical characteristics of the Tresca criterion and the Mises criterion are revealed from the perspective of square shear stress, and a new yield criterion with generality is established by introducing a weighting coefficient δ . The yield criterion can be transformed to various yield criteria with different δ, including the existing yield criteria. On this basis, the plastic failure analysis of a pipe elbow is carried out, and the analytical formula of the burst pressure is derived, in which the strain hardening effect of the material is also considered. Besides, the main parameters that affect the burst pressure are analyzed. It is shown that the theoretical burst pressures calculated by the present yield criterion with different δ can coincide well with the experimental values for different materials, and the burst pressures decrease with the increase of the strain hardening exponent, while increase with the increase of the thickness-diameter ratio. The burst pressure formula established in this paper is of great significance to the structural design and safety assessment of a pipe elbow. Highlights: A weighted unification yield criterion that has generality is derived in terms of square shear stresses. The burst pressure formula based on the new yield criterion can suit for various pipeline materials. The burst pressure formular imbedding the strain hardening exponent can provide more reasonable results.